A Cross Sectional study of Cephalic Index to Determine Sexual Variation in male and female MBBS and BDS Students of a Tertiary Care Teaching hospital in North East India - Adhikari , U; Phanjoubam , M; Frieny, L (Journal of Indian Academy of Forensic Medicine, 2024)
phalic (short headed). Cephalometric studies can also be carried Anthropometric characteristics have direct relationship with sex, shape and form of an individual and these factors are intimately linked with each other and are a manifestation of the internal structure and tissue components which in turn, are influenced by environmental and genetic factors. Cephalic Index is useful for identification of race. It is also used to determine sexual differences especially in individuals human remains found in Europe. It is one of the clinical whose identities are unknown. A research study was conducted with an aim to determine cephalic index of MBBS and BDS students of a tertiary care teaching hospital in North East India and to compare sexual variation. A total of 480 MBBS and BDS students participated in the study with a ratio of 2:1. The mean age of the participants was 21 ± 2 years. Male participants were more in number than female with 2:1 ratio. Students belonging to all Northeastern States participated in the study with fewer from All India quota. The mean cephalic index was 82.07 ± 2.61 ranging from 72.43 to 84.21. The CI of female was more than male students and it was found to be statistically significant (p=0.02). The Brachycephalic type is the commonest cephalic index in both sexes (73.5% in male and 64.8% in female) respectively pattern. Further, cephalic index is the most frequently followed by Mesaticephalic (24.6% in male and 33.3% in female). Dolicocephalic is least common type of cephalic index. However, brachycephalic CI is higher in male participants and mesaticephalic CI is higher in female participants and this difference is found to be statistically significant.